Doubly-Crossing Syllables:: Thomas O’Grady on Poetry, Exile, and Ireland - Compton, Anne (Studies in Canadian Literature / Études en littérature canadienne)

(untitled) (The University of New Brunswick, 2001)
The interview focuses largely on Thomas O'Grady's first collection of poetry What Really Matters. He discusses ideas of home and exile, Prince Edward Island and Island literature, the idea of language and its relation to place, family history, and academics. O'Grady's use of the formalist and the Romantic tradition is considered.